Efficacy of Adalimumab in a Girl with Refractory Intestinal Behcet’s Disease - Mariko Kaji; Takayuki Kishi; Takako Miyamae; Satoru Nagata; Hisashi Yamanaka; Satoshi Fujikawa (Case Reports in Rheumatology)
We describe our experience with a juvenile patient who had refractory intestinal Behcet’s disease that responded to adalimumab, a fully humanized antibody against soluble TNF-α and its receptor. The patient, a 13-year-old girl, presented with oral aphthous ulcers, vulvar pain, and rashes on the lower extremities. She gradually developed a low-grade fever, abdominal pain, diarrhea, and hematochezia. Lower gastrointestinal endoscopy revealed ulcers in the terminal ileum, consistent with intestinal Behcet’s disease. Methylprednisolone pulse therapy was initiated, after which the symptoms transiently improved, but, during the corticosteroid taper, the abdominal pain recurred. The symptoms resolved soon after the administration of adalimumab. Of importance, the dose of corticosteroids was successfully reduced without exacerbation during 8 months of observation. This is the first reported case in which adalimumab was used for pediatric gastrointestinal Behcet’s disease. Adalimumab is a good choice for intestinal Behcet’s disease refractory to conventional treatment.